A matter of wording: Microsoft moves carefully to shore up China business. - Forney, Matt; Fluendy, Simon; Thornton, Emily (Far Eastern Economic Review, 1996)
Microsoft's swift move to head off a potential disaster when Beijing officials discovered the phrase “communist bandits” embedded in the Windows 1995 Chinese-character selection system is part of the company's new, conciliatory approach on the Chinese mainland. Microsoft is tying up with key companies in China's computer industry and offering help to China's software designers. Microsoft now dominates desktop PC operating systems in China and is becoming a serious contender in large-scale systems.